2019
DOI: 10.14569/ijacsa.2019.0100780
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Concerns in Online Social Networks: A Users’ Perspective

Abstract: Social networking has elevated the human life to the heights of interaction, response and content sharing. It has been offering state of the art facilities to its users for a long time. Though, over the period of time, the systems have become quite matured yet alongside the benefits, multiple concerns of the user with regard to the privacy and information security also exist. Multidimensional threat spectrum to the Internet has also been posed to social networking tools. A lot of work is being done to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…Leisure refers to the extent to which individuals use social media for entertainment and relaxation. Social interaction refers to the extent to which individuals use social media to connect and communicate with others (Lee & Ahn, 2010) Studies have shown that perceived benefits play a significant role in shaping privacy disclosure on social media (Ali et al, 2019). For example, Raza et al (2019) found that individuals who use social media to connect and communicate with others are more likely to disclose personal information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Leisure refers to the extent to which individuals use social media for entertainment and relaxation. Social interaction refers to the extent to which individuals use social media to connect and communicate with others (Lee & Ahn, 2010) Studies have shown that perceived benefits play a significant role in shaping privacy disclosure on social media (Ali et al, 2019). For example, Raza et al (2019) found that individuals who use social media to connect and communicate with others are more likely to disclose personal information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social interaction refers to the extent to which individuals use social media to connect and communicate with others (Lee & Ahn, 2010) Studies have shown that perceived benefits play a significant role in shaping privacy disclosure on social media (Ali et al, 2019). For example, Raza et al (2019) found that individuals who use social media to connect and communicate with others are more likely to disclose personal information. Another study, Khan & Qureshi (2016) found that individuals who use social media as a source of information are more likely to disclose personal information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past, we lacked a systematic approach and specialized knowledge for investigating cybercrime. There was a lack of established protocol, resulting in frequent release of the criminals (Ali, Malik et al 2019). The government created a National Response Center for Cybercrime, which operates under the supervision of the Federal Investigation Agency (FIA).…”
Section: Cybercrime In Pakistanmentioning
confidence: 99%
“…But the most important access control for OSN is Relationship-Based, as the whole social network is based on relations of the users. A survey on SN privacy is presented in [91] and a detailed survey on access control for SN is presented in [92]. In this survey, we are discussing Relationship-Based Access Control in detail.…”
Section: Access Control Models For Online Social Network (Osn)mentioning
confidence: 99%